Gendering social mobility: a comparative perspective on the nexus of education and class in Europe - Abrantes, P.; Abrantes, M. (Gender and Education, 2014)
Research on social mobility typically acknowledges the relevance of gender. However, gender-based differences still lack extensive description and explanation. This article starts by reviewing a number of influential contributions on social mobility, educational systems and employment change, as well as important critiques raised in feminist scholarship with regard to these topics of enquiry. We argue that class analysis should not only document asymmetry between men and women in greater detail, but also incorporate it as a piece of explanatory value in the understanding of social mobility at large. This is attempted by examining the data of the European Social Survey covering 22 countries. Drawing on this large-scale data set, we will demonstrate that the transformation of employment structures favours particular forms of upward mobility, which coexist with the resilience of gender inequality in accessing affluent classes. The impact of gender on the nexus between social background, educational attainment and class position is far from uniform in Europe, with significant variation across classes, countries and fields of study.